Exploring students' conceptual understanding on impluse and linear momentum using the 5E instructional model - Mirando, Melissa E. (Animo Repository, 2005)
This paper determined the potential of 5E (Engagement, Exploration, Elaboration, Explanation and Evaluation) Instructional Model in promoting student's conceptual understanding on impulse and linear momentum in high school physics at Tanay National High School, Tanay, Rizal for the SY 2003-2004. Thirty-two students from the first two sections were randomly selected to be the subject of the study. The pretest was administered two weeks prior to instruction and the posttest was given on the last day of instruction. Open-ended questions, group task tests, oral test and concept development practice and problem-solving exercise were administered to assess further student's understanding. A comparison of the pretest and posttest performance indicated that there was a significant improvement in the student's performance in terms of their level of understanding on impulse and linear momentum. With a mean gain of 48.02%, the study revealed that the 5E Instructional Model was potentially effective in bringing about conceptual understanding. Results of the group task test in the exploration phase showed that students gained better understanding on the mathematical definition of momentum, with the highest mean score of 5.7 as revealed in the group tasks scored using the scoring rubrics. Oral test in the explanation phase revealed that Group II and III had almost demonstrated an exemplary understanding on impulse and momentum. They were able to define momentum operationally and mathematically by relating an objects mass and velocity. With a mean score of 5.7 appropriately, adequately and correctly inter-related the concepts involved in impulse and linear momentum. Whereas, two groups were categorized as transitional with satisfactory responses and with serious flaws but nearly satisfactory understanding respectively was obtained by group I and IV.